PAULUS SEBAGAI SKENOPOIOS, TEOLOGI KEMAH LUKAS, DAN MISI APOSTOLIKNYA - Nggadas, Deky Hidnas Yan (Jurnal Teologi RAI, 2024)
Recent studies of Paul as a tentmaker tend to emphasize its applications to frontlier missions and entrepreneurship. In this paper, using historical-grammatical exegesis and biblical theological observations, I argue that these emphases are difficult to justify. Luke potraits Paul as a tentmaker in the context of his tabernacle theology that was closely intertwined with Paul's apostolic mission.